Debt Management Performance Assessment : Nigeria - World Bank (Washington, DC, 2014)
The DeMPA is a methodology for assessing public debt management performance through a comprehensive set of indicators spanning the full range of government debt management functions. The DeMPA tool presents debt performance indicators along with a scoring methodology. This report pertains to a debt management performance assessment of Nigeria in 2012. Areas with very high scores include the managerial set-up, evaluation of debt management operations, as well as domestic and external borrowing practices. There have been substantial improvements in management of operational risks, demonstrated by the availability of procedures manuals and data security and back-ups, and in debt reporting.